(untitled) (Studia Prawnicze / The Legal Studies, 2014)
Konwencja Wiedeńska, czyli Konwencja Narodów Zjednoczonych o umowach międzynarodowej sprzedaży towarów (ang. United Nations Convention on Contracts of the International Sale of Goods – CISG, „Konwencja”) dotyczy umów sprzedaży ruchomości pomiędzy podmiotami, prowadzącymi działalność handlową w państwach-stronach Konwencji, bądź w sytuacji, gdy normy prawa prywatnego międzynarodowego wskazują na ustawodawstwo państwa-strony Konwencji (art. 1 ust. 1 lit. a-b). Reguluje trzy kwestie: zawarcia umowy, obowiązków kupującego i sprzedającego oraz przysługujących im środków ochrony. Zasadniczo stosuje się ją do obrotu profesjonalnego (art. 1 i 2). The United Nations Convention on Contracts for the International Sale of Goods (the so-called Vienna Convention, CISG) is considered one of the most important and influential private law acts of the past decades. The most compelling evidence of the impact of the CISG is the European private law. It is especially evident in case of consumer sales law of the European Union. The Consumer Sales Directive (99/44) and, to some extent, even the Directive on Consumer Rights (2011/83/EC) were based on principles and institutions derived from the CISG. The most important influences are of course the objective liability of a debtor and the institution of conformity of the goods; however, even the basic terms (such as “conformity of goods” and “non-conformity of goods”) are defined per analogiam. And even though European legislator did not borrow from the CISG its’ concept of the fundamental breach of contract, the further cases of CISG’s impact are seen in cases of Nachfrist and remedies available to the parties of a contract. Since European consumer sales law is one of the most important spheres of EU interests and influences national civil law systems, CISG may easily be described as the model and backbone of future private law harmonization.